UWM Today - Mack, Nancy A. (My University, 2005)
UWM Today is the magazine of the University of Wisconsin - Milwaukee Alumni Association. This issue contains articles about men's basketball coach Bruce Pearl, UWM's involvement with the WiSys Patents system, and Kenilworth makeover project.
Keywords: Alumni; Newsletter